YOU CAN USE MY NAME; YOU DON'T HAVE TO STEAL MY STORY - A CRITIQUE OF ANONYMITY IN INDIGENOUS STUDIES - SVALASTOG, ANNA-LYDIA; ERIKSSON, STEFAN (Developing world bioethics, 2010)
ABSTRACT Our claim in this paper is that not being identified as the data source might cause harm to a person or group. Therefore, in some cases the default of anonymisation should be replaced by a careful deliberation, together with research subjects, of how to handle the issues of identification and confidentiality. Our prime example in this article is community participatory research and similar endeavours on indigenous groups. The theme, content and aim of the research, and the question of how to handle property rights and ownership of research results, as well as who should be in charge of the research process, including the process of creating anonymity, should all be answered, before anonymity is accepted.